Strategi Manajemen Memori pada Sistem Operasi Android untuk Smartphone Kelas Menengah - Tri Putra Aditya; Aisyah Aisyah; Rakhmadi Rahman (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
In the context of rapidly evolving mobile technology, memory management has become an important aspect that determines the efficiency and effectiveness of Android operating systems, particularly on mid- range smartphones. The objective of this research is to identify, analyze and develop memory management strategies that can improve the performance of the Android operating system on resource-constrained devices. Using an experimental approach, this study evaluates various memory management techniques, including the use of optimized caches, memory compression, and page replacement algorithms, to determine the most effective combination to improve system responsiveness and performance. The results show that the implementation of appropriate memory management strategies can significantly improve operating system performance and user experience while extending battery life. These findings provide valuable information for application developers and device manufacturers to optimize their products for mid-range smartphone competition.